Health-care professional’s attitude, beliefs and perceived potential barriers for recommended adult immunization practices in patients with type-2 diabetes mellitus - Yeluri, Seshagiri Rao; Gara, Himavathy K.; Vamsi, Gadde Sai Surya; Vanamali, Dharma Rao (International Journal of Research in Medical Sciences, 2020)
Background: Immunization coverage remains very low among adults. Vaccine preventable diseases (VPDs) may have an unpredictable course in diabetes mellitus (DM) owing to their altered immune functions. The objective of the study was to analyse the knowledge, attitude, practices and behaviour of the healthcare professionals (HCPs) regarding the pneumococcal, influenza and hepatitis B vaccination in patients of type-2 DM. Methods: This was a community based, cross-sectional study focusing on HCPs who were involved in diabetic care and were aware about recommended guidelines of adult immunization program. 100 HCPs completed this survey which embraced various parameters involved in vaccine uptake. Results: Females constituted 34% of the participating HCPs. The HCPs with qualification of MBBS and MD were 51% and 49% respectively. MD HCPs were routinely vaccinating DM patient more than MBBS ones which was statistically significant. Difficulty in identifying patients eligible for vaccination was perceived by 53% of HCPs. Vaccination was believed to be more important in children than adults by 63% HCPs and 93% agreed that vaccination provided protection against VPDs. Perceived as barriers for vaccination were: urgent concerns of the patients (79%), lack of time for explaining (49%), vaccine safety (60%), cost of vaccine (58%), lack of records (65%), lack of recall system (62%), lack of educational material for patients (83%), lack of training for HCPs (75%) and lack of ‘standing orders’ (84%). Conclusions: Despite recommendations for adult immunization, there are many substantial lacunae in knowledge and practice among HCPs resulting in low immunization coverage. A structured approach encompassing education and training, identification and elimination of potential barriers and improving infrastructure and leadership is the need to curb the mortality and morbidity associated with VPDs in diabetics.